(untitled) (Literary Voice, 2025)
The present article explores Tagore’s concept of freedom against the backdrop of Tagore-Gandhi debate on ‘charkha,’ the role of science and technology in Indian context, and the concept of Nationalism. These concerns of Tagore are evidently manifest in the play, Muktadhara as the author analyses the writer’s ‘meditations’ on the frailties of State sponsored educational system and the imposition of science on humanity, thus causing horrible imbalance in man-nature equations.